Bovine Tuberculosis in a Nebraska Herd of Farmed Elk and Fallow Deer: A Failure of the Tuberculin Skin Test and Opportunities for Serodiagnosis. (30th March 2011) - Waters, W. Ray; Stevens, Gary E.; Schoenbaum, Mark A.; Orloski, Kathy A.; Robbe-Austerman, Suelee; Harris, N. Beth; Hall, S. Mark; Thomsen, Bruce V.; Wilson, Arach J.; Brannian, Roger E.; Nelson, Jeffrey T.; Schafer, Shawn; et al.
Abstract : In 2009, Mycobacterium bovis infection was detected in a herd of 60 elk ( Cervus elaphus ) and 50 fallow deer ( Dama dama ) in Nebraska, USA. Upon depopulation of the herd, the prevalence of bovine tuberculosis (TB) was estimated at 71–75%, based upon histopathology and culture results. Particularly with elk, gross lesions were often severe and extensive. One year ago, the majority of the elk had been tested for TB by single cervical test (SCT), and all were negative. After initial detection of a tuberculous elk in this herd, 42 of the 59 elk were tested by SCT. Of the 42 SCT-tested elk, 28 were TB-infected with only 3/28 reacting upon SCT. After SCT, serum samples were collected from the infected elk and fallow deer from this herd at necropsy and tested by three antibody detection methods including multiantigen print immunoassay, cervidTB STAT-PAK, and dual path platform VetTB (DPP). Serologic test sensitivity ranged from 79 to 97% depending on the test format and host species. Together, these findings demonstrate the opportunities for use of serodiagnosis in the rapid detection of TB in elk and fallow deer.